Manual single lumen alternating micro-batch dialysis achieves reliable clearance via diffusion - Ceschia, Giovanni; Chawla, Apaara K.; Morgan, Jolyn; Rose, James E.; Goldstein, Stuart L.; Hasson, Denise C. (Pediatric research, 2023)
Background Acute kidney injury is a cause of preventable deaths in low resource settings due to lack of dialysis access and cost. A manual single lumen alternating micro-batch (mSLAMB) dialysis technique performs kidney replacement therapy using single lumen access, low-cost bags/tubing, intravenous fluids, and a filter without electricity, a battery, or a pump. We propose a protocol whereby mSLAMB can perform diffusive clearance simply and efficiently to bring dialysis to underserved populations. Methods Expired packed red blood cells mixed with crystalloid solution were spiked with urea and anticoagulated with heparin. A Static diffusion Technique (with short flushes of fluid before each filter pass) was compared to a Dynamic diffusion Technique (with fluid running through the filter during the forward pass) to assess urea and potassium clearance. Passive ultrafiltration was the difference between the 200 mL batch volume and volume returned to the blood bag per cycle. Results Five cycles achieved urea reduction ratios (URR) between 17–67% and potassium clearance of 18–60%, with higher percentages achieved from higher proportions of batch volume dialyzed to patient volume. Dynamic Technique increased clearance over the Static Technique. Passive ultrafiltration volumes were 2.5–10% of batch volume. Conclusion mSLAMB dialysis performs diffusive clearance and passive ultrafiltration efficiently, while preserving resources and available manpower. Impact mSLAMB is a dialysis technique that can perform efficient diffusive clearance and passive ultrafiltration without electricity, batteries, or a pump. With basic medical supplies and limited manpower, mSLAMB is a cost-effective means of providing emergency dialysis in low resource areas. We propose a basic algorithm for safe and cost-effective dialysis for people of different ages and sizes.